Peran Bahasa Indonesia dalam Komunikasi Bisnis terhadap Penurunan Frekuensi Kunjungan Konsumen di Pasar Kalimadu - Agustin, Puspita Dian; Laki, Sinta; Laboro, Nadin; Anatasia, Disti; Darban, Syaila Riandi; Topae, Nur Vanissa; Djiki, Rahmawati; Halim, Farel; Baruadi, Ronald; Latief, Akbar; Lagarusu, Tri Julianto S.; Yasin, Pratiwi Mufliha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the role of the Indonesian language in business communication regarding the decline in consumer visit frequency at Kalimadu Market. The research employed a qualitative descriptive method using in-depth interviews, observation, and documentation as data collection techniques. The findings reveal that the Indonesian language plays a vital role in establishing social relations and creating comfortable interactions between sellers and buyers. However, most traders still focus more on product quality than on communication strategies, resulting in underutilized linguistic effectiveness. The use of mixed languages Indonesian and local dialects also creates communication inconsistencies. Therefore, improving communication competence through polite and effective use of Indonesian is essential to enhance market appeal and customer loyalty.